(3MGTjI GdeWhds - (3Ydj ehTLis; (3GdSYO GdJaJGRGfj , SYO GdOjf eSYhO Hf YeQ Hf YHO Gddg GdJaJGRGfj,J (B793 (3g` s
(3ChdgG (B:s
(3GdMeO ddg eNJQY eG gjGJ GdCTjGA hghjGJgG GdeWdY Ydi cdjGJ GdGehQ s
(3BNQgG (B:s
(3VQhQI Cf LejY GdbjhO ZjQ GdaGYd jLH Cf jchf gPg MGTjI GdeWhd ddehdi GdeMbb ehdGfG Ydi ehTLi fYeg Gddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B6s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3hQO ai cTa GdXfhf L(B1 (3U` (B474 (3Cf GdeWhd gh deDdag SYO GdOjf eSYhO Hf YeQ GdJaJGRGfi GdeJhai SfI (B791(3g` s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B219 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B228 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B430s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdeLGejYs